Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.